2010
DOI: 10.1016/j.jpowsour.2009.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Surface structural disordering in graphite upon lithium intercalation/deintercalation

Abstract: We report on the origin of the surface structural disordering in graphite anodes induced by lithium intercalation and deintercalation processes. Average Raman spectra of graphitic anodes reveal that cycling at potentials that correspond to low lithium concentrations in Li x C (0 ≤ x < 0.16) is responsible for most of the structural damage observed at the graphite surface. The extent of surface structural disorder in graphite is significantly reduced for the anodes that were cycled at potentials where stage-1 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
219
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(229 citation statements)
references
References 32 publications
10
219
0
Order By: Relevance
“…[14][15][16][17][18][19] This wide range can be attributed to different kinds of graphite used in these studies in addition to different techniques used to extract the diffusion coefficient. Model predictions would suggest that for the lower value of diffusion coefficient (1.0 × 10 −14 m 2 /s) particle cracking during delithiation becomes likely at moderate C-rates (1 C based on the theoretical capacity of graphite), for particle of 14 μm diameter.Although studies have suggested that graphite disorder increases with cycling, 20 and that the electrode can undergo mechanical damage, 21 literature studies do not show evidence of graphite particles themselves cracking. While modeling studies have shown that graphite cracking is possible, no experimental studies have been reported that indicate this mode of degradation at the particle scale, suggesting a disparity between the model predictions and the experimental observation.…”
mentioning
confidence: 98%
“…[14][15][16][17][18][19] This wide range can be attributed to different kinds of graphite used in these studies in addition to different techniques used to extract the diffusion coefficient. Model predictions would suggest that for the lower value of diffusion coefficient (1.0 × 10 −14 m 2 /s) particle cracking during delithiation becomes likely at moderate C-rates (1 C based on the theoretical capacity of graphite), for particle of 14 μm diameter.Although studies have suggested that graphite disorder increases with cycling, 20 and that the electrode can undergo mechanical damage, 21 literature studies do not show evidence of graphite particles themselves cracking. While modeling studies have shown that graphite cracking is possible, no experimental studies have been reported that indicate this mode of degradation at the particle scale, suggesting a disparity between the model predictions and the experimental observation.…”
mentioning
confidence: 98%
“…Inspection of Fig. 7f and j also reveal an additional peak at a potential of 3.45 V. Based on the information provided within [47,48], this new peak is most likely resulting from a phase change in the earlier lithiation process of the graphite electrode. This decrease of the OCV is directly related to the increase in energy capacity.…”
Section: Duty-cycle Studymentioning
confidence: 82%
“…At 0% SOC, the graphite electrode is almost completely delithiated. During charging, Li + ions intercalate into the graphite layers and the material transitions through several phases as the lithium content within the material increases [47,48]. One of these phase transitions is indicated in the peak around a full cell potential of 3.52 V in Fig.…”
Section: Duty-cycle Studymentioning
confidence: 98%
“…During charge/discharge cycling or storage of LIBs, aging effects may occur [7]. Mechanical degradation like graphite exfoliation or surface structural disordering leads to loss of mobile lithium or self-discharge [8][9][10][11]. One of the main reasons for exfoliation is the cointercalation of solvated lithium ions.…”
Section: Introductionmentioning
confidence: 99%